Revisiting asthma therapeutics: focus on WNT signal transduction. Issue 1 (January 2018) - Koopmans, Tim; Gosens, Reinoud
Highlights: Asthma risk results in part from genotype-specific responses to environmental exposures. This highlights genes important in early life and lung development. A potential candidate is the WNT signalling pathway. Evidence has implicated both β-catenin-dependent and β-catenin-independent WNT axes with asthma. Its deregulation is important for inflammation, airway remodelling, and airway hyperresponsivess. WNT-based trials for cancer are ongoing, which may present valuable lessons for asthma future therapies. Abstract : Asthma is a complex disease of the airways that develops as a consequence of both genetic and environmental factors. This interaction has highlighted genes important in early life, particularly those that control lung development, such as the Wingless/Integrase-1 (WNT) signalling pathway. Although aberrant WNT signalling is involved with an array of human conditions, it has received little attention within the context of asthma. Yet it is highly relevant, driving events involved with inflammation, airway remodelling, and airway hyper-responsiveness (AHR). In this review, we revisit asthma therapeutics by examining whether WNT signalling is a valid therapeutic target for asthma. Teaser: WNT signalling is a relevant, yet underappreciated pathway in asthma. Recent insights into the pathology of asthma have highlighted this pathway as a potential novel therapeutic point of intervention. With this in mind, we attempt to answer the question: is WNT signalling a valid target for asthma therapy?